Music Genre and Subcultural Artwork on the Post-war British Fairground. (2nd October 2018) - Trowell, Ian
Abstract : This article gives a historical account of the intricate crossover between pop music and the British fairground, focusing on the evolving visual resources of pop music and how these came to be utilised on the fairground. The visual identity of the fairground – expressed predominantly through painted work – reflects the fairground as a subcultural space for music, and draws from the iconography of pop music and subcultural strands. This gives British fairground art a unique character and vibrant, expressive essence. A start point is taken as the formative music styles and associated imagery in the period 1950–1980, proposing a parallel to the Pop Art movement arising through the 1960s. The 1980s are examined through the lens of transmediality, i.e. a non-media specific interpretation, and the crossover between music and horror exemplified by Michael Jackson's song "Thriller". Finally, the 1990s to the present are documented as a new mode of image production and representation, with iconography from the Rave movement in dance music and subculture becoming the ubiquitous visual syntax of the fairground. The article considers the process of translation between the visual resources of two realms of popular culture with particular regard to the challenge presented by popular music to be translated into fairground art and the evolving structure of fairground machinery and its affordance of fairground art.